Blood B Cell Depletion Reflects Immunosuppression Induced by Live-Attenuated Infectious Bursal Disease Vaccines - Courtillon, Céline; Allée, Chantal; Amelot, Michel; Keita, Alassane; Bougeard, Stéphanie; Härtle, Sonja; Rouby, Jean-Claude; Eterradossi, Nicolas; Soubies, Sebastien Mathieu (Frontiers in Veterinary Science, 2022)
Immunosuppression in poultry production is a recurrent problem worldwide and one of the major viral immunosuppressive agents is Infectious Bursal Disease Virus (IBDV). Infections by IBDV are mostly controlled through the use of live-attenuated vaccines. Live-attenuated Infectious Bursal Disease (IBD) vaccine candidates are classified, based on their residual immunosuppressive properties, as “mild”, “intermediate”, “intermediate-plus” or “hot”. The immunosuppression protocol described by the European Pharmacopoeia (Ph. Eur.) uses a lethal Newcastle Disease Virus (NDV) infectious challenge to measure the interference of a given IBDV vaccine candidate on NDV vaccinal immune response. A Ph. Eur. - derived protocol was thus implemented to quantify immunosuppression induced by one mild, two intermediate and four intermediate-plus live-attenuated IBD vaccines as well as a pathogenic viral strain. This protocol confirmed the respective immunosuppressive properties of those vaccines and virus. In the search for a more ethical alternative to Ph. Eur. - based protocols, two strategies were explored. First, ex vivo viral replication of those vaccines and the pathogenic strain in stimulated chicken primary bursal cells was assessed. Replication levels were not strictly correlated to immunosuppression observed in vivo. Second, changes in blood leukocyte counts in chicks during a Ph. Eur. - type protocol prior to lethal NDV challenge was followed. There, the drop in B cells counts was more severe in the case of intermediate-plus vaccines. Counting blood B cells may thus represent a highly quantitative, faster and more ethical strategy than NDV challenge to assess the immunosuppression induced in chickens by live-attenuated IBD vaccines.